2019
DOI: 10.2174/1574888x14666181205120110
|View full text |Cite
|
Sign up to set email alerts
|

Stem Cells and Endometrial Regeneration: From Basic Research to Clinical Trial

Abstract: Monthly changes in the endometrial cycle indicate the presence of endometrial stem cells. In recent years, various stem cells that exist in the endometrium have been identified and characterized. Additionally, many studies have shown that Bone Marrow Mesenchymal Stem Cells (BM-MSCs) provide an alternative source for regenerating the endometrium and repairing endometrial injury. This review discusses the origin of endometrial stem cells, the characteristics and main biomarkers among five types of putative endom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
34
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(38 citation statements)
references
References 99 publications
0
34
0
Order By: Relevance
“…When compared with traditional MSCs, ERCs have certain advantages, such as abundant resource, noninvasive collection methods, reusing human waste, and easy to large-scale expansion capability. In addition, ERCs were also reported with the ability in modulating immune response and lack of immunogenicity [11]. Previous studies from our research group and others have reported that ERC-mediated stem cell therapy could modulate the immune response in the treatment of a series of diseases, such as stroke, myocardial infarction, ischemia reperfusion injury, inflammatory bowel disease, and multiple organ dysfunction syndrome [12].…”
Section: Introductionmentioning
confidence: 95%
“…When compared with traditional MSCs, ERCs have certain advantages, such as abundant resource, noninvasive collection methods, reusing human waste, and easy to large-scale expansion capability. In addition, ERCs were also reported with the ability in modulating immune response and lack of immunogenicity [11]. Previous studies from our research group and others have reported that ERC-mediated stem cell therapy could modulate the immune response in the treatment of a series of diseases, such as stroke, myocardial infarction, ischemia reperfusion injury, inflammatory bowel disease, and multiple organ dysfunction syndrome [12].…”
Section: Introductionmentioning
confidence: 95%
“…After the damaged hEndoSC coculturing with MSCs in vitro, MSCs significantly increased the rate of proliferation and decreased apoptosis [9]. And many patients had already been pregnant after the transplantation of MSCs with collagen scaffolds [10,11].…”
Section: Introductionmentioning
confidence: 99%
“…As stated by Padykula, 28 the resident stem-like cell population migrates and gives rise to a group of progenitor cells that become committed to specific types of cell differentiation, for example, epithelial, stromal, and vascular cells, within certain microenvironments. 29 Studies of the various endometrial progenitor/stem cells and their markers have been reviewed by others 5,[30][31][32] and are outlined in Table 1. Endometrial stem cells have been described as a powerful tool for clinical and therapeutic applications.…”
Section: Stem Cell Populations In the Human Endometriummentioning
confidence: 99%